PENGEMBANGAN MEDIA PEMBELAJARAN TEKS CERITA ULANG BERMUATAN TOKOH LOKAL PADA PEMBELAJARAN BAHASA INDONESIA - Herza Alwanny; M. Oky Fardian Gafari; Abdurrahman Adisahputera (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2020)
Abstract: This study aims to: (1) describe the feasibility of developing learning media for recount texts containing local figures, and (2) describe the results of the development of learning media for recount texts containing local figures in the form of integrated media that is websites. This research method is Research and Development (R&D) with a 4-D model (Define, Design, Develop, and Disseminate). The results showed that: (1) validation of material experts with an average of 85.25% on very good criteria; (2) expert validation of instructional media design with an average of 91.25% on very good criteria, (3) individual trials with an average of 75% with good criteria , (4) small group trials with an average of 82.5% with very good criteria, and (5) limited field group trials with an average of 93% with very good criteria. The final activity of developing instructional media is continued by observing student learning outcomes in rewriting the recount text containing local figures. The learning outcomes of the recount text writing test before using learning media were 73.85, while using learning media increased by 86.05. Difference of 12.2 from before to after using media. This proves that the learning media for recount texts containing local figures that are developed can improve student learning outcomes.Abstrak: Penelitian ini bertujuan: (1) mendeskripsikan kelayakan pengembangan media pembelajaran teks cerita ulang bermuatan tokoh lokal, dan (2) mendeskripsikan hasil pengembangan media pembelajaran teks cerita ulang bermuatan tokoh lokal berupa media yang dipadukan dalam bentuk website. Metode penelitian ini adalah Research and Development (R&D) dengan model 4-D (Define, Design, Develop, and Disseminate). Hasil penelitian menunjukkan bahwa: (1) validasi ahli materi dengan rata-rata 85.25% pada kriteria sangat baik; (2) validasi ahli desain media pembelajaran dengan rata-rata 91.25% pada kriteria sangat baik, (4) uji coba perorangan dengan rata-rata 75% dengan kriteria baik, dan (5) uji coba kelompok lapangan terbatas dengan rata-rata 93% dengan kriteria sangat baik. Kegiatan akhir dari pengembangan media pembelajaran ini dilanjutkan dengan melihat hasil belajar siswa dalam menulis kembali teks cerita ulang bermuatan tokoh lokal. Hasil belajar tes menulis teks cerita ulang sebelum menggunakan media pembelajaran sebesar 73.85, sedangkan menggunakan media pembelajaran meningkat sebesar 86.05. Selisih 12.2 dari sebelum ke sesudah menggunakan media. Hal ini membuktikan bahwa media pembelajaran teks cerita ulang bermuatan tokoh lokal yang dikembangkan dapat meningkatkan hasil belajar siswa.